Unification modulo presburger arithmetic and other decidable theories - Ayala Rincón, Mauricio; Tavares Araújo, Ivan E. (Revista Colombiana de Computación, 2001)
We present a general uni cation algorithm modulo Presburger Arithmetic for a re- stricted class of modularly speci ed theories where function symbols of the target theory have non arithmetic codomain sorts. Additionally, we comment on conditions guaran-teeing decidability of matching and uni cation problems modulo more general theories than the arithmetic ones, which appear when automated deduction is implemented by combining conditional rewriting techniques and decision algorithms for built-in predi- cates.